Cardiogenic Shock: Protocols, Teams, Centers, and Networks - Alex F Warren; Carolyn Rosner; Raghav Gattani; Alex G Truesdell; Alastair G Proudfoot (US Cardiology Review)
The mortality of cardiogenic shock (CS) remains unacceptably high. Delays in the recognition of CS and access to disease-modifying or hemodynamically stabilizing interventions likely contribute to poor outcomes. In parallel to successful initiatives in other disease states, such as acute ST-elevation MI and major trauma, institutions are increasingly advocating the use of a multidisciplinary ‘shock team’ approach to CS management. A volume–outcome relationship exists in CS, as with many other acute cardiovascular conditions, and the emergence of ‘shock hubs’ as experienced facilities with an interest in improving CS outcomes through a hub-and-spoke ‘shock network’ approach provides another opportunity to deliver improved CS care as widely and equitably as possible. This narrative review outlines improvements from a networked approach to care, discusses a team-based and protocolized approach to CS management, reviews the available evidence and discusses the potential benefits, challenges, and opportunities of such systems of care.